THERMODYNAMIC AND PHASE BEHAVIOR STUDY OF FLUID AND CLATHRATE HYDRATE FOR C02 RICH GAS MIXTURE - NASIR, QAZI (2015)
The rapid increase in demand and pnce of natural gas has put an enormous pressure on the suppliers to ensure its availability in the market. This has created incentives for the development of infrastructure to produce natural gas from gas reservoirs rich in carbon dioxide (C02) content. Producing natural gas from these reservoirs is challenging, economically unviable and requires further information about the thermodynamic properties of the reservoir fluid, including its phase behavior. Therefore, exploration and production from natural gas fields containing high carbon dioxide up to 80% require accurate phase behavior data for classification of the type of the gas, monitoring of flow in transportation pipelines and determination of separation strategy of carbon dioxide from the natural gas.